Autoimmune polyglandular syndrome type 3: A case report of an unusual presentation and literature review. Issue 2 (4th February 2022) - Apolinario, Michael; Brussels, Aaron; Cook, Curtiss B.; Yang, Shaun
Abstract: Autoimmune polyglandular syndromes (APS) are rare disorders characterized by auto‐destruction of endocrine and non‐endocrine organs by organ‐specific antibody‐directed T‐lymphocytic infiltration. This case highlights a 29‐year‐old Caucasian man with vitiligo found to have significant neurological abnormalities in the setting of newly diagnosed pernicious anemia and thyroid autoimmune disease. Abstract : Autoimmune polyglandular syndromes can have widely variable presentations. If a patient is found to have newly diagnosed thyroid autoimmune disease, it would be valuable to screen for other autoimmune diseases such as pernicious anemia; as these associated endocrinopathies can lead to significant neurological consequences.